Research handbook on sustainable co-operative enterprise case studies of organisational resilience in the co-operative business model - edited by Tim Mazzarol (Cheltenham Edward Elgar, 2014)
Co-operatives are found in all industry sectors and almost all countries around the world. However, despite their significant economic and social contributions, the academic literature has largely ignored these important businesses. This book is a detailed examination of the co-operative enterprise business model and the factors that help to enhance its sustainability and resilience, as well as those forces that lead to its destruction.
Includes bibliographical references and index.
Keywords: Cooperative societies